A nano-modified formaldehyde-free wall paint and preparation method thereof
Through Mo doping and SiO2 coating of modified Ag-TiO2 nanoparticle composite porous polyimide fiber material, the stability problem of nano-modified net aldehyde wall paint in temperature changing environment is solved, and excellent aldehyde removal performance and stability are achieved.
Patent Information
- Application Number
- CN202510819892.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-19
- Publication Date
- 2025-08-12
- Estimated Expiration
- 2045-06-19
AI Technical Summary
Nanomodified net aldehyde wall paint has accumulated coating interface stress and increased porosity caused by temperature changes in plateau areas, affecting its application stability and aldehyde removal effect.
Modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is used to form a stable interface structure through Mo doping and SiO2 coating, which enhances the temperature change stability of the coating and the exposure of active sites, and maintains the stability of the coating structure using the network structure of the porous polyimide fiber.
It significantly improves the application stability and aldehyde removal effect of nano-modified net aldehyde wall paint in temperature changing environments, ensuring high exposure and long-term effectiveness of active sites.
Smart Images

Figure ULQOBI18TQ5ENW2ELGHSAYABOTTAQ9EJN5GCTSH9 
Figure Z3VWI2R5Q5AIMKRIMF5IQ5UNV4MLXXUX1NEI13FG
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and more specifically, to a nano-modified formaldehyde-free wall paint and a preparation method thereof. Background Art
[0002] Nano-modified formaldehyde-free wall paint is a new type of wall paint that combines nanotechnology and environmentally friendly materials. It has a variety of excellent performance and environmentally friendly characteristics. It is suitable for various indoor environments, especially places that require high environmental standards and long-term residence, such as homes, hospitals, schools and hotels. Its excellent mildew-proof, antibacterial and stain-resistant properties enable it to perform well in these places and can maintain a clean and healthy indoor environment for a long time.
[0003] The raw materials for nano-modified formaldehyde-free wall paint primarily include polymer emulsion, pigments and fillers, additives, and nano-formaldehyde-free materials. The polymer emulsion is the foundation of the wall paint, providing adhesion and durability. Currently, water-based polymer emulsions are mostly used, as they are environmentally friendly and environmentally friendly. Pigments and fillers adjust the paint's color and texture, enhancing its purification effect and stability. Additives improve the paint's application performance and storage stability. The nano-formaldehyde-free materials continuously decompose organic pollutants such as formaldehyde and toluene, converting them into harmless substances. Currently, Ag-TiO2 nanoparticles are a commonly used nano-formaldehyde-free material. Their main components are TiO2 photocatalysts and nano-silver ions. They actively adsorb formaldehyde and decompose it into carbon dioxide and water. This not only effectively removes formaldehyde, but also achieves a high formaldehyde removal rate of up to 99.4%. Furthermore, the adsorption and decomposition functions of Ag-TiO2 nanoparticles can last for over three years without saturation and without secondary pollution. This allows for continuous and effective formaldehyde removal over long-term use, providing long-term protection for family health.
[0004] Regarding the above-mentioned related technologies, the inventors believe that in some special application areas, such as plateau areas, the temperature difference between morning, noon and evening varies greatly. Under repeated temperature increase and decrease cycles, due to the significant difference in thermal expansion coefficient between the coating matrix material and the Ag-TiO2 nanoparticles, when the temperature changes, shear stress is caused at the interface due to the different expansion / contraction amplitudes. The stress continues to accumulate in multiple cycles and exceeds the interface bonding strength threshold, which will eventually cause the Ag-TiO2 nanoparticles to fall off; at the same time, temperature changes cause the gas in the coating pores to expand and contract, causing the coating porosity to increase, which in turn leads to the obstruction of the formaldehyde diffusion path and the reduction of the accessibility of the active sites; the above will lead to poor application stability of the nano-modified formaldehyde-free wall paint.
[0005] Therefore, it is urgent to propose a solution to solve the above technical problems. Summary of the Invention
[0006] In order to improve the application stability of nano-modified formaldehyde-free wall paint in a temperature-changing environment, the present application provides a nano-modified formaldehyde-free wall paint and a preparation method thereof.
[0007] In the first aspect, the present application provides a nano-modified formaldehyde-free wall paint, which adopts the following technical solution:
[0008] A nano-modified formaldehyde-free wall paint comprises the following raw materials in parts by weight:
[0009] 60-90 parts of water-based acrylic emulsion;
[0010] 25-35 parts water;
[0011] 7-15 parts of filler;
[0012] 8-16 parts of pigment;
[0013] 2-4 parts of additives;
[0014] 2.5-5.5 parts of modified Ag-TiO2 nanoparticle composite porous polyimide fiber material;
[0015] The modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is prepared by the following steps:
[0016] S1. Ag nanoparticles are dispersed in an ethanol solution of tetrabutyl titanate, and molybdenum acetylacetonate is added and mixed. Nitric acid is added to adjust the pH to 3-4 and the mixture is stirred for reaction at a temperature of 60-70° C. for 2-3 h. After the reaction, the mixture is calcined at 450-550° C. for 1.5-2 h to obtain intermediate particles.
[0017] S2. Dispersing the intermediate particles in an ethanol solution, adding ammonia water to adjust the pH to 9-10, then adding a mixture of ethyl orthosilicate and anhydrous ethanol to disperse the mixture, reacting at 30-40° C. for 4-6 hours, and then adjusting the pH to neutral with hydrochloric acid to obtain a mixed dispersion;
[0018] S3. Spray the mixed dispersion onto the surface of the porous polyimide fiber through atomization, and sequentially dry at 110-130° C. for 40-60 min and heat treat at 350-400° C. for 1-2 h to obtain a modified Ag-TiO2 nanoparticle composite porous polyimide fiber material.
[0019] By adopting the above technical solution, in the preparation of modified Ag-TiO2 nanoparticle composite porous polyimide fiber material, first, in step S1, using Ag nanoparticles as active sites, through the hydrolysis and condensation of tetrabutyl titanate and the addition of molybdenum acetylacetonate, after subsequent calcination, Ag-TiO2 composite particles doped with molybdenum, i.e., intermediate particles, are formed. By introducing Mo doping, the temperature change stability of the Ag-TiO2 interface is improved, and the stress accumulation caused by the difference in thermal expansion coefficient can be reduced, thereby effectively alleviating the interface stress; secondly, in step S2, SiO2 is formed on the surface of the intermediate particles through the action of tetraethyl orthosilicate. The coating structure can inhibit the oxidation or agglomeration of the intermediate particles in a temperature-changing environment, prevent the inactivation of active sites, and provide more adsorption sites, which is conducive to enriching formaldehyde molecules on the surface of the intermediate particles; then in step S3, the mixed dispersion is evenly deposited on the fiber surface and pores by atomization, and in the subsequent processing process, the intermediate particles can not only be stably bound to the fiber surface through Si-O-Ti chemical bonds and physical anchoring, but can also use the SiO2 on their own surface to form Si-OC bonds with the surface of the polyimide fiber, thereby reducing the interface peeling caused by temperature fluctuations and synergistically bringing about an improvement in temperature-change resistance. By applying the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material prepared above to nano-modified formaldehyde-free wall paint, a network reinforcement structure is formed in the coating structure through the anisotropy of the fiber, thereby maintaining the stability of the coating structure in a temperature-changing environment. At the same time, when affected by temperature changes, it can exert excellent synergistic effects through the doping of Mo, the surface coating of SiO2 and the temperature-resistant carrier of the porous polyimide, thereby exerting excellent and stable formaldehyde removal performance, and finally obtaining a nano-modified formaldehyde-free wall paint with significant application stability in a temperature-changing environment.
[0020] Preferably, in the step S1 of preparing the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material, the molar ratio of Ag, Ti and Mo in the obtained intermediate particles is (3-5):100:(0.5-1).
[0021] By adopting the above technical solution, the obtained molybdenum-doped Ag-TiO2 composite particles can not only reduce the stress accumulation caused by the difference in thermal expansion coefficient, effectively relieve the interface stress, and ensure the stability of the application binding state under the temperature change environment, but also reduce the interference of temperature fluctuations on the reaction path, and avoid particle agglomeration during the binding process, ensuring high exposure of active sites, thereby ensuring that the final modified Ag-TiO2 nanoparticle composite porous polyimide fiber material can exert a stable and better formaldehyde removal effect after application even if it is affected by the temperature change environment.
[0022] Preferably, in the step S2 of preparing the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material, the ratio of the intermediate particles, tetraethyl orthosilicate and anhydrous ethanol is 1 g: (7-10) mL: (1-3) mL.
[0023] By adopting the above technical solution, the formation of large particles or agglomerates can be avoided during the reaction process of step 2, so that the silica layer is deposited on the surface of the intermediate particles in an orderly manner, achieving efficient coating and stable performance of the intermediate particles, and having high dispersibility, high temperature stability and photocatalytic activity retention ability, thereby being able to exert a stable and better corresponding effect, which is conducive to finally obtaining a nano-modified formaldehyde-free wall paint with better application quality in a temperature-changing environment.
[0024] Preferably, in the step S3 of preparing the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material, the mass ratio of the mixed dispersion to the porous polyimide fiber is (4-6):1.
[0025] By adopting the above technical scheme, the above ratio enables the mixed dispersion to fully penetrate into the micropores of the polyimide fiber, and can prevent the pores of the porous polyimide fiber from being completely blocked, maintain the specific surface area of the porous polyimide fiber, and ensure the integrity of the gas diffusion channel; at the same time, it can also eventually form a multi-level pore structure on the porous polyimide fiber, ensure high exposure of the active sites, and effectively adsorb formaldehyde; in this way, the temperature-change adaptability of the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is better, and thus a nano-modified formaldehyde-free wall paint with excellent and stable formaldehyde removal effect is obtained.
[0026] Preferably, in the preparation step S3 of the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material, the porous polyimide fiber has a pore size of 180-220 nm, a porosity of 75-85%, a fiber diameter of 15-25 μm, a fiber length of 1-5 mm, and a specific surface area of 80-100 m 2 / g.
[0027] By adopting the above technical solution and utilizing the porous polyimide fibers of the above specifications, the mixed dispersion can form a gradient-distributed load structure on the surface of the porous polyimide fibers after being combined with the porous polyimide fibers, and ensure that a through three-dimensional network channel is formed inside the fibers, thereby effectively increasing the active site density and reducing particle shedding, achieving the synergy of high load, high protection and high performance, thereby enabling the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material to exhibit a more stable combined formaldehyde removal effect under a temperature-changing environment, which is conducive to ultimately obtaining a nano-modified formaldehyde-free wall paint of better quality.
[0028] Preferably, the filler is one or a combination of calcium carbonate, barium sulfate, barite powder, kaolin, talc, silica powder, mica powder and quartz powder.
[0029] By adopting the above technical solution, the filler can fill the gaps in the polymer network formed by the water-based acrylic emulsion, thereby improving the hardness, wear resistance, scrub resistance and other properties of the coating. The above types of fillers are all suitable for the preparation of nano-modified formaldehyde-free wall paints, and can be selected and combined according to the needs of actual application scenarios, thereby obtaining a variety of nano-modified formaldehyde-free wall paints with strong overall applicability.
[0030] Preferably, the auxiliary agent is one or a combination of several of a dispersant, a defoamer, a leveling agent, a wetting agent, a film-forming aid, a preservative, a thickener and an adhesion promoter.
[0031] By adopting the above technical solution, the additives work synergistically in three aspects: processing stability regulation, film quality optimization, and durability enhancement, ensuring that the nano-modified formaldehyde-free wall paint has high dispersibility, excellent surface quality, and long-lasting functionality; and the above-mentioned types of additives are all suitable for the preparation of nano-modified formaldehyde-free wall paint, and can exert better corresponding effects, ensuring that the final nano-modified formaldehyde-free wall paint has better quality.
[0032] In a second aspect, the present application provides a method for preparing a nano-modified formaldehyde-free wall paint, which adopts the following technical solution:
[0033] A method for preparing a nano-modified formaldehyde-free wall paint comprises the following steps:
[0034] (1) preparing raw materials including water-based acrylic emulsion, water, filler, pigment, additive and modified Ag-TiO2 nanoparticle composite porous polyimide fiber material according to the ratio;
[0035] (2) After the auxiliary agent and water in step (1) are mixed, a water-based acrylic resin emulsion is added for mixing and dispersion, and then a filler and a modified Ag-TiO2 nanoparticle composite porous polyimide fiber material are added for mixing and dispersion, and finally a pigment is added for mixing and dispersion to obtain a nano-modified formaldehyde-free wall paint.
[0036] By adopting the above technical solution, the above preparation method is simple to operate, and the raw materials are added in steps. This not only facilitates quality control during the process, but also allows the raw materials to fully combine and cooperate to exert their excellent effects, thereby obtaining a nano-modified formaldehyde-free wall paint with excellent and stable quality. Furthermore, the above preparation method of the nano-modified formaldehyde-free wall paint is also suitable for large-scale industrial production.
[0037] In summary, this application has the following beneficial effects:
[0038] This application adds specially prepared modified Ag-TiO2 nanoparticle composite porous polyimide fiber material to nano-modified formaldehyde-free wall paint, and utilizes Mo doping, SiO2 surface coating and the temperature-resistant carrier of porous polyimide to exert excellent synergistic effects. Even if affected by the temperature-changing environment, it can still exert a stable and better formaldehyde removal effect, thereby significantly improving the application stability of nano-modified formaldehyde-free wall paint in a temperature-changing environment. DETAILED DESCRIPTION
[0039] The present application is further described in detail below with reference to preparation examples, embodiments and comparative examples.
[0040] Unless otherwise specified, the raw materials used in the preparation examples, embodiments and comparative examples of the present application are all commercially available.
[0041] The water-based acrylic emulsion was purchased from BASF HPD 196 MEA AP water-based acrylic resin emulsion;
[0042] The additives are composed of defoaming agent, leveling agent, film-forming agent and dispersant in a weight ratio of 0.5:1.5:3:2, wherein the defoaming agent is purchased from BYK-021 defoaming agent of Germany, the leveling agent is purchased from BYK-349 leveling agent of Germany, the film-forming agent is purchased from Eastman film-forming agent TEXANOL alcohol ester twelve, and the dispersant is purchased from BYK-190 dispersant of Germany;
[0043] The filler is obtained by mixing light calcium carbonate and talc in a weight ratio of 1:1. Both light calcium carbonate and talc are purchased from Shijiazhuang Chenjin Mineral Products Co., Ltd., wherein the light calcium carbonate specification is 1250 mesh and the talc specification is 800 mesh.
[0044] Ag nanoparticles were purchased from Suzhou Kaifa New Material Technology Co., Ltd. with a particle size of 20 nm;
[0045] The pigment was purchased from BASF as K6902 Phthalocyanine Blue.
[0046] Preparation examples of raw materials and / or intermediates
[0047] Preparation Example 1
[0048] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is prepared by the following steps:
[0049] S1. Ag nanoparticles were dispersed in an ethanol solution of tetrabutyl titanate, and molybdenum acetylacetonate was added and mixed. Nitric acid was added to adjust the pH to 3.5 and stirred for reaction. The reaction temperature was 65° C. and the reaction time was 2.5 h. After completion, the mixture was calcined at 500° C. for 1.75 h to obtain intermediate particles.
[0050] S2. Dispersing the intermediate particles in 4 times the volume of ethanol solution, adding ammonia water to adjust the pH to 9.5, then adding a mixed solution of ethyl orthosilicate and anhydrous ethanol to disperse, reacting at 35° C. for 5 hours, and then adjusting the pH to neutral with hydrochloric acid to obtain a mixed dispersion;
[0051] S3. The mixed dispersion is sprayed onto the surface of the porous polyimide fiber by atomization, and is dried at 120° C. for 50 min and heat-treated at 375° C. for 1.5 h to obtain a modified Ag-TiO2 nanoparticle composite porous polyimide fiber material.
[0052] Note: In the above operation, in step S1, the molar ratio of Ag, Ti and Mo in the intermediate particles obtained is 4:100:0.75. In step S2, the ratio of intermediate particles, tetraethyl orthosilicate and anhydrous ethanol is 1g: 8.5mL: 2mL. In step S3, the mass ratio of the mixed dispersion and porous polyimide fiber is 5:1; the porous polyimide fiber has a pore size of 200nm, a porosity of 80%, a fiber diameter of 20μm, a fiber length of 3mm, and a specific surface area of 90m 2 / g.
[0053] During the actual operation, the ethanol solution is first poured into the reaction container, and the volume of the ethanol solution in the reaction container and the corresponding scale value are recorded. Then the intermediate particles are added, and the volume increase of the mixed material in the container is obtained through the change of the scale value of the reaction container, until the "intermediate particles are dispersed in 4 times the volume of ethanol solution" is achieved.
[0054] Preparation Example 2
[0055] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that it is prepared by the following steps:
[0056] S1. Ag nanoparticles were dispersed in an ethanol solution of tetrabutyl titanate, and molybdenum acetylacetonate was added and mixed. Nitric acid was added to adjust the pH to 3 and stirred for reaction. The reaction temperature was 60°C and the reaction time was 3 hours. After completion, the mixture was calcined at 450°C for 2 hours to obtain intermediate particles.
[0057] S2. Dispersing the intermediate particles in 4 times the volume of an ethanol solution, adding ammonia water to adjust the pH to 9, then adding a mixed solution of ethyl orthosilicate and anhydrous ethanol to disperse the mixture, reacting at 30° C. for 6 hours, and then adjusting the pH to neutral with hydrochloric acid to obtain a mixed dispersion;
[0058] S3. The mixed dispersion is sprayed onto the surface of the porous polyimide fiber by atomization, and is dried at 110° C. for 60 min and heat-treated at 350° C. for 2 h to obtain a modified Ag-TiO2 nanoparticle composite porous polyimide fiber material.
[0059] Preparation Example 3
[0060] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that it is prepared by the following steps:
[0061] S1. Ag nanoparticles were dispersed in an ethanol solution of tetrabutyl titanate, and molybdenum acetylacetonate was added and mixed. Nitric acid was added to adjust the pH to 4 and stirred for reaction. The reaction temperature was 70°C and the reaction time was 2 hours. After completion, the mixture was calcined at 550°C for 1.5 hours to obtain intermediate particles.
[0062] S2. Dispersing the intermediate particles in 4 times the volume of ethanol solution, adding ammonia water to adjust the pH to 10, then adding a mixture of ethyl orthosilicate and anhydrous ethanol to disperse, reacting at 40° C. for 4 hours, and then adjusting the pH to neutral with hydrochloric acid to obtain a mixed dispersion;
[0063] S3. The mixed dispersion is sprayed onto the surface of the porous polyimide fiber by atomization, and is dried at 130° C. for 40 minutes and heat-treated at 400° C. for 1 hour to obtain a modified Ag-TiO2 nanoparticle composite porous polyimide fiber material.
[0064] Preparation Example 4
[0065] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that, in step S1, the molar ratio of Ag, Ti and Mo in the obtained intermediate particles is 3:100:0.5.
[0066] Preparation Example 5
[0067] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that, in step S1, the molar ratio of Ag, Ti and Mo in the obtained intermediate particles is 5:100:1.
[0068] Preparation Example 6
[0069] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that, in step S2, the ratio of intermediate particles, tetraethyl orthosilicate and anhydrous ethanol is 1g: 7mL: 1mL.
[0070] Preparation Example 7
[0071] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that, in step S2, the ratio of intermediate particles, tetraethyl orthosilicate and anhydrous ethanol is 1g: 10mL: 3mL.
[0072] Preparation Example 8
[0073] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that, in step S3, the mass ratio of the mixed dispersion and the porous polyimide fiber is 4:1.
[0074] Preparation Example 9
[0075] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that, in step S3, the mass ratio of the mixed dispersion and the porous polyimide fiber is 6:1.
[0076] Preparation Example 10
[0077] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that, in step S3, the porous polyimide fiber has a pore size of 180 nm, a porosity of 75%, a fiber diameter of 15 μm, a fiber length of 1 mm, and a specific surface area of 80 m 2 / g.
[0078] Preparation Example 11
[0079] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that, in step S3, the porous polyimide fiber has a pore size of 220 nm, a porosity of 85%, a fiber diameter of 25 μm, a fiber length of 5 mm, and a specific surface area of 100 m 2 / g.
[0080] Preparation Example 12
[0081] A modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is different from Preparation Example 1 in that it is prepared by the following steps:
[0082] S1. Ag nanoparticles were dispersed in an ethanol solution of tetrabutyl titanate, and nitric acid was added to adjust the pH to 3.5 for stirring and reacting at a temperature of 65°C for 2.5 hours. After the reaction, the mixture was calcined at 500°C for 1.75 hours to obtain intermediate particles.
[0083] S2, dispersing the intermediate particles in 4 times the volume of ethanol solution to obtain a mixed dispersion;
[0084] S3. The mixed dispersion is sprayed onto the surface of the porous polyimide fiber by atomization, and is dried at 120° C. for 50 min and heat-treated at 375° C. for 1.5 h to obtain a modified Ag-TiO2 nanoparticle composite porous polyimide fiber material.
[0085] Preparation Example 13
[0086] A modified Ag-TiO2 nanoparticle is different from that in Preparation Example 1 in that it is prepared by the following steps:
[0087] Ag nanoparticles were dispersed in an ethanol solution of tetrabutyl titanate, and then molybdenum acetylacetonate was added and mixed. Nitric acid was added to adjust the pH to 3.5 and stirred for reaction. The reaction temperature was 65°C and the reaction time was 2.5h. After completion, the product was calcined at 500°C for 1.75h.
[0088] Preparation Example 14
[0089] A modified Ag-TiO2 nanoparticle is different from that in Preparation Example 1 in that it is prepared by the following steps:
[0090] S1. Ag nanoparticles were dispersed in an ethanol solution of tetrabutyl titanate, and nitric acid was added to adjust the pH to 3.5 for stirring and reacting at a temperature of 65°C for 2.5 hours. After the reaction, the mixture was calcined at 500°C for 1.75 hours to obtain intermediate particles.
[0091] S2. Disperse the intermediate particles in 4 times the volume of ethanol solution, add ammonia water to adjust the pH to 9.5, then add a mixed solution of tetraethyl orthosilicate and anhydrous ethanol to disperse, react at 35°C for 5 hours, then adjust the pH to neutral with hydrochloric acid to obtain a mixed dispersion, collect the product by centrifugation, and calcinate at 400°C for 1 hour to obtain.
[0092] Preparation Example 15
[0093] A kind of Ag-TiO2 nanoparticles, which is different from Preparation Example 1 in that the Ag nanoparticles are dispersed in an ethanol solution of tetrabutyl titanate, nitric acid is added to adjust the pH to 3.5 and stirred for reaction, the reaction temperature is 65°C, the reaction time is 2.5h, and then calcined at 500°C for 1.75h to obtain.
[0094] Example
[0095] Example 1
[0096] A nano-modified formaldehyde-free wall paint, the raw materials used in its preparation and their corresponding weight parts are shown in Table 1, and it is prepared by the following steps:
[0097] (1) preparing raw materials including water-based acrylic emulsion, water, filler, pigment, additive and modified Ag-TiO2 nanoparticle composite porous polyimide fiber material according to the ratio;
[0098] (2) After the auxiliary agent and water in step (1) are mixed, a water-based acrylic resin emulsion is added for mixing and dispersion, and then a filler and a modified Ag-TiO2 nanoparticle composite porous polyimide fiber material are added for mixing and dispersion, and finally a pigment is added for mixing and dispersion to obtain a nano-modified formaldehyde-free wall paint.
[0099] Note: In the above operation, the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 1.
[0100] Example 2-3
[0101] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the raw materials used in its preparation and their corresponding weight parts are shown in Table 1.
[0102] Table 1 Raw materials used in the preparation of Examples 1-3 and their corresponding weight parts (parts / kg)
[0103]
[0104] Example 4
[0105] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 2.
[0106] Example 5
[0107] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 3.
[0108] Example 6
[0109] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 4.
[0110] Example 7
[0111] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 5.
[0112] Example 8
[0113] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 6.
[0114] Example 9
[0115] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 7.
[0116] Example 10
[0117] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 8.
[0118] Example 11
[0119] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 9.
[0120] Example 12
[0121] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 10.
[0122] Example 13
[0123] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 11.
[0124] Comparative Example
[0125] Comparative Example 1
[0126] A nano-modified formaldehyde-free wall paint is different from Example 1 in that the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is obtained from Preparation Example 12.
[0127] Comparative Example 2
[0128] A nano-modified formaldehyde-free wall paint, which differs from Example 1 in that the mass of the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is replaced by the modified Ag-TiO2 nanoparticles obtained in Preparation Example 13.
[0129] Comparative Example 3
[0130] A nano-modified formaldehyde-free wall paint, which differs from Example 1 in that the mass of the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is replaced by the modified Ag-TiO2 nanoparticles obtained in Preparation Example 14.
[0131] Comparative Example 4
[0132] A nano-modified formaldehyde-free wall paint, which differs from Example 1 in that the mass of the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is replaced by the Ag-TiO2 nanoparticles obtained in Preparation Example 15.
[0133] Performance testing
[0134] Test samples: The nano-modified formaldehyde-free wall paint obtained in Examples 1-13 was selected as test sample 1-13, and the nano-modified formaldehyde-free wall paint obtained in Comparative Example 1-4 was selected as control sample 1-4.
[0135] Test method: Formaldehyde purification efficiency test: Refer to the method described in JC / T 1074-2021 "Purification Performance of Indoor Air Purification Functional Coating Materials" to test the formaldehyde purification efficiency of nano-modified formaldehyde-free wall paint. The coating thickness is 200μm. At an indoor temperature of 25°C, the measured formaldehyde purification efficiency value is recorded as A. The test period is 24 hours.
[0136] The same nano-modified formaldehyde-free wall paint was simultaneously used to conduct the above formaldehyde purification efficiency test. Temperature changes were applied within the 24-hour test period. Specifically, the initial temperature was 25°C, and the temperature was first increased to 50°C at 2.5°C / min and maintained for 10 minutes. The temperature was then decreased to -10°C at 1.5°C / min and maintained for 10 minutes. The temperature was then decreased to 25°C at 3.5°C / min, and this cycle was repeated for 18 cycles. The formaldehyde purification efficiency value measured in the test was recorded as B.
[0137] Finally, the loss ratio of the purification efficiency value is calculated. The loss ratio of the purification efficiency value = (AB) / A. The smaller the loss ratio of the purification efficiency value, the better the formaldehyde removal stability of the nano-modified formaldehyde-free wall paint under temperature-changing environment.
[0138] After performing the above tests on test samples 1-13 and control samples 1-4, the test results are recorded in Table 2.
[0139] Table 2 Test results of test samples 1-13 and control samples 1-4
[0140]
[0141] Combining Example 1 and Comparative Examples 1-4 and Table 2, it can be seen that the present application can significantly improve the application stability of nano-modified formaldehyde-free wall paint in a temperature-changing environment by adding a specially prepared modified Ag-TiO2 nanoparticle composite porous polyimide fiber material to the nano-modified formaldehyde-free wall paint. The loss ratio of the purification efficiency value obtained by the above test is significantly reduced. It is also found that compared with the application of Ag-TiO2 nanoparticle raw materials in the control sample 4, if the use of Mo doping, SiO2 surface coating and any of the temperature-resistant carriers of the porous polyimide is selected One of them is combined with Ag-TiO2 nanoparticles. After being applied to nano-modified formaldehyde-free wall paint, although it can improve the formaldehyde removal stability of the modified formaldehyde-free wall paint in a temperature-changing environment, the improvement is limited, and the sum of the improvement effects brought by the application of each of the three situations is far less than the excellent improvement effect brought by their mutual synergy. It can be seen that in the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material, the use of Mo doping, SiO2 surface coating and porous polyimide temperature-resistant carrier can exert excellent synergistic effects, with an overall significant improvement effect.
[0142] In combination with Example 1 and Examples 4-13 and Table 2, it can be seen that in the preparation of the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material, "in step S1, the molar ratio of Ag, Ti and Mo in the obtained intermediate particles is (3-5):100: (0.5-1)", "in step S2, the ratio of the intermediate particles, tetraethyl orthosilicate and anhydrous ethanol is 1 g: (7-10) mL: (1-3) mL", and "in step S3, the mass ratio of the mixed dispersion and the porous polyimide fiber is (4-6):1; the pore size of the porous polyimide fiber is 180-220 nm, the porosity is 75-85%, the fiber diameter is 15-25 μm, the fiber length is 1-5 mm, and the specific surface area is 80-100 m 2 / g", both can enable the modified Ag-TiO2 nanoparticle composite porous polyimide fiber material to exhibit a more stable combined formaldehyde removal effect under a temperature-changing environment, which is conducive to finally obtaining a nano-modified formaldehyde-free wall paint with better quality.
[0143] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make non-creative modifications to the present embodiment as needed, but as long as they are within the scope of the claims of the present application, they are protected by the patent law.
Claims
1. A nano-modified formaldehyde-free wall paint, characterized in that: Made from the following raw materials in parts by weight: 60-90 parts of water-based acrylic emulsion; 25-35 parts water; 7-15 parts of filler; 8-16 parts of pigment; 2-4 parts of additives; 2.5-5.5 parts of modified Ag-TiO2 nanoparticle composite porous polyimide fiber material; The modified Ag-TiO2 nanoparticle composite porous polyimide fiber material is prepared by the following steps: S1. Ag nanoparticles are dispersed in an ethanol solution of tetrabutyl titanate, molybdenum acetylacetonate is added and mixed, and nitric acid is added to adjust the pH to 3-4 for stirring and reacting at a temperature of 60-70°C for 2-3 hours. After the reaction, the mixture is calcined at 450-550°C for 1.5-2 hours to obtain intermediate particles; the molar ratio of Ag, Ti, and Mo in the obtained intermediate particles is (3-5):100:(0.5-1); S2. Disperse the intermediate particles in an ethanol solution, add ammonia water to adjust the pH to 9-10, then add a mixture of tetraethyl orthosilicate and anhydrous ethanol to disperse the mixture, react at 30-40°C for 4-6 hours, and then adjust the pH to neutral with hydrochloric acid to obtain a mixed dispersion; the ratio of the intermediate particles, tetraethyl orthosilicate, and anhydrous ethanol is 1 g: (7-10) mL: (1-3) mL; S3. The mixed dispersion is sprayed onto the surface of the porous polyimide fiber by atomization, and then dried at 110-130°C for 40-60 min and heat-treated at 350-400°C for 1-2 h to obtain a modified Ag-TiO2 nanoparticle composite porous polyimide fiber material; the mass ratio of the mixed dispersion to the porous polyimide fiber is (4-6):1; the porous polyimide fiber has a pore size of 180-220 nm, a porosity of 75-85%, a fiber diameter of 15-25 μm, a fiber length of 1-5 mm, and a specific surface area of 80-100 m 2 / g.
2. The nano-modified formaldehyde-free wall paint according to claim 1, characterized in that: The filler is one or a combination of calcium carbonate, barium sulfate, barite powder, kaolin, talc powder, silica powder, mica powder and quartz powder.
3. The nano-modified formaldehyde-free wall paint according to claim 1, characterized in that: The auxiliary agent is one or a combination of several of a dispersant, a defoamer, a leveling agent, a wetting agent, a film-forming auxiliary agent, a preservative, a thickener and an adhesion promoter.
4. The method for preparing the nano-modified formaldehyde-free wall paint according to claim 1, wherein: The following steps are involved: (1) preparing raw materials including water-based acrylic emulsion, water, filler, pigment, additive and modified Ag-TiO2 nanoparticle composite porous polyimide fiber material according to the ratio; (2) After the auxiliary agent and water in step (1) are mixed, a water-based acrylic resin emulsion is added for mixing and dispersion, and then a filler and a modified Ag-TiO2 nanoparticle composite porous polyimide fiber material are added for mixing and dispersion, and finally a pigment is added for mixing and dispersion to obtain a nano-modified formaldehyde-free wall paint.
Citation Information
Patent Citations
Antibacterial formaldehyde-removing art coating and preparation method thereof
CN119192931A
Nanometer RuAg / heterojunction MoO3 / TiO2 composite catalyst as well as preparation method and application thereof
CN119259043A